Promoting Energy Efficiency: Barriers, Societal Needs and Policies - Della Valle, Nives; Bertoldi, Paolo (Frontiers in Energy Research, 2022)
The Climate Change urgency requires a swift reduction of energy consumption. One way to achieve this is through increased energy efficiency. Over the past decades, the debate on how to encourage energy efficiency has been guided by the physical–technical–economic model, which has a strong focus on technologies and cost savings, and in which human behaviour has been seen as a trivial factor. However, the advent of behavioural economics has started enabling the integration of the human factor also into energy efficiency policy. This integration is however only in its infancy. While the perspectives taken by economics and behavioural sciences enable to capture the individual dimension of energy efficiency as a problem of individual choice, the collective and social aspect of energy efficiency is still largely overlooked on the energy policy agenda. With its emphasis on how social structures interpenetrate individual actions and construction of reality, sociology offers an additional important insight that goes beyond the identification of barriers‐drivers underlying investment choices. This paper aims to increase policy makers’ awareness of complementary disciplinary resources, on which they can draw to better define and address the problems associated to energy efficiency. Second, it provides a case to develop an interdisciplinary perspective as a basis to develop a more scientifically valid and socially relevant energy efficiency policy advice.